2013
DOI: 10.1186/1749-799x-8-3
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic performance of neuromuscular electrical stimulation (NMES) during recovery from total hip arthroplasty

Abstract: BackgroundPatients post total hip arthroplasty (THA) remain at high risk of developing Deep Vein Thrombosis (DVT) during the recovery period following surgery despite the availability of effective pharmacological and mechanical prophylactic methods. The use of calf muscle neuromuscular electrical stimulation (NMES) during the hospitalised recovery period on this patient group may be effective at preventing DVT. However, the haemodynamic effectiveness and comfort characteristics of NMES in post-THA patients imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 27 publications
0
45
0
4
Order By: Relevance
“…In Warwick et al, 35 the geko device was active for 5 min in each position and the median VAS score and VRS across all positions were 2.5 and 2, respectively. Consistent with these, Broderick et al 36 reported that the mean VAS score at start and end of 4 h electrical stimulation were 2.3 and 3.6, respectively. In Broderick et al, 40 the mean VAS score after 2 h and 4 h of stimulation were 2.7 and 2.8, respectively.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In Warwick et al, 35 the geko device was active for 5 min in each position and the median VAS score and VRS across all positions were 2.5 and 2, respectively. Consistent with these, Broderick et al 36 reported that the mean VAS score at start and end of 4 h electrical stimulation were 2.3 and 3.6, respectively. In Broderick et al, 40 the mean VAS score after 2 h and 4 h of stimulation were 2.7 and 2.8, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…However, the incidence of DVT in patients with malignant disease was significantly lower Williams et al 23 Geko T-1 1 70-560 ms 2 7 N R Izumi et al 24 SEN-52901 10 NR NR 100 Jawad et al 25 Geko T-1 1 70-560 ms 2 7 N R Warwick et al 35 Geko T-1 1 0-400 ms 2 7 N R Broderick et al 36 Duo Williams et al 23 Izumi et al 24 Jawad et al 25 Goyal et al 26 Velmahos et al 27 Merli et al 29 Bostrom et al 30 Lindströ m et al 28 Doran et al 31 Doran and White 32…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, we hypothesized that attaching EMS on the lower limbs might have a potential to produce a similar effect of exercise therapy even for the patients forced to be immobile for prolonged periods. Some reports suggest that EMS may have a preventive effect on DVT not only in healthy subjects [8] but also in total knee/hip arthroplasty patients [11, 12] and postoperative patients [13]. However, a report on EMS use in patients with major trauma failed to show a significant difference in the rate of DVT formation and venous flow parameters between the patients with and without EMS [14].…”
Section: Introductionmentioning
confidence: 99%